Prevalence assessment of sexually transmitted infections among pregnant women visiting an antenatal care center of Nepal: Pilot of the World Health Organization's standard protocol for conducting STI prevalence surveys among pregnant women. - Rubee Dev; Shambhu P Adhikari; Anjana Dongol; Surendra K Madhup; Pooja Pradhan; Sunila Shakya; Shrinkhala Shrestha; Sneha Maskey; Melanie M Taylor (PLoS ONE)
Introduction Sexually transmitted infections (STIs) are common during pregnancy and can result in adverse delivery and birth outcomes. The purpose of this study was to estimate the prevalence of STIs; Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Treponema pallidum (syphilis), Trichomonas vaginalis (trichomoniasis), and Human Immunodeficiency Virus (HIV) among pregnant women visiting an antenatal care center in Nepal. Materials and methods We adapted and piloted the WHO standard protocol for conducting a prevalence survey of STIs among pregnant women visiting antenatal care center of Dhulikhel Hospital, Nepal. Patient recruitment, data collection, and specimen testing took place between November 2019-March 2020. First catch urine sample was collected from each eligible woman. GeneXpert platform was used for CT and NG testing. Wet-mount microscopy of urine sample was used for detection of trichomoniasis. Serological test for HIV was done by rapid and enzyme-linked immunosorbent assay tests. Serological test for syphilis was done using "nonspecific non-treponemal" and "specific treponemal" antibody tests. Tests for CT, NG and trichomoniasis were done as part of the prevalence study while tests for syphilis and HIV were done as part of the routine antenatal testing. Results 672 women were approached to participate in the study, out of which 591 (87.9%) met the eligibility criteria and consented to participate. The overall prevalence of any STIs was 8.6% (51/591, 95% CI: 6.3-10.8); 1.5% (95% CI: 0.5-2.5) for CT and 7.1% (95% CI: 5.0-9.2) for trichomoniasis infection. None of the samples tested positive for NG, HIV or syphilis. Prevalence of any STI was not significantly different among women, age ≤ 24 years (10%, 25/229) compared to women age ≥25 years (7.1%, 26/362) (p = 0.08). Conclusions The prevalence of trichomoniasis among pregnant women in this sub-urban population of Nepal was high compared to few cases of CT and no cases of NG, syphilis, and HIV. The WHO standard protocol provided a valuable framework for conducting STI surveillance that can be adapted for other countries and populations.